Thinning and recovery effects on soil properties in two sites of a Mediterranean forest, in Cuenca Mountain (South-eastern of Spain) (Forest Ecology and Management, 2013)
Thinning effects on soil microbial activity and biomass in two sites of a Mediterranean forest, in Cuenca Mountain (South-eastern of Spain), were compared 2–6 years following treatments. In order to study changes in these properties, five plots were established; three plots in mature natural site dominated by Pinus pinaster and Quercus ilex and two plots post-wildfire natural regeneration site dominated by Quercus ilex. In each site, a silviculture treatment of thinning had been previously carried out, while the other was left as a forest control. Soil samples were taken during the dry season (July 2010) and after the first autumn rains (October 2010). The experiment consisted on a nested factorial design with two factors: the site (two levels: mature natural and regenerated) and thinning treatment nested within site effect (three levels in mature natural site: control, thinned in 2002 and thinned in 2004, and two levels within regenerated site: control and thinned in 2008).Several sensitive variables related to the soil microbial activity such as soil respiration and biomass carbon and some enzyme activities (urease, phosphatase, β-glucosidase and dehydrogenase) were evaluated. Physical and chemical soil variables (organic matter, total nitrogen, phosphorus, pH, conductivity and carbonates) were also measured. These variables of forest soil in autumn were highest that in summer. Also the results showed that thinning have a significant effect on soil microbiological variables and soil enzymatic activities. Thinning operations tended to alter soil variables and highly reduced the organic matter content. A significant correlation was also found between microbiological and biochemical variables and physic chemical variables, organic matter and total nitrogen. Adaptative management forest plans should consider these results in order to achieve sustainable forest management, especially in the context of soil quality and Mediterranean forest subjected to wildfire disturbances.